2022
DOI: 10.1002/mds.29268
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitating Cough Dysfunction in Parkinson's Disease: A Randomized Controlled Trial

Abstract: A BS TRACT: Background: Disorders of airway protection (cough and swallowing) are pervasive in Parkinson's disease (PD) resulting in a high incidence of aspiration pneumonia and death. However, there are no randomized controlled trials comparing strength and skill-based approaches to improve airway protection in PD. Objectives: The aim of this study was to compare expiratory muscle strength training (EMST) and sensorimotor training for airway protection (smTAP) to improve coughrelated outcomes in people with P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 47 publications
0
36
0
Order By: Relevance
“…A preliminary study investigating the feasibility of smTAP in patients with progressive supranuclear palsy (PSP) showed a significant increase in peak expiratory flow rate (PEFR) after one session of smTAP which supports the feasibility and highlights the potential for further use in the future 10 . Furthermore, a recently published randomized controlled trial showed the superior efficacy of smTAP over EMST on improving reflex and voluntary cough 20 …”
Section: Introductionmentioning
confidence: 78%
See 4 more Smart Citations
“…A preliminary study investigating the feasibility of smTAP in patients with progressive supranuclear palsy (PSP) showed a significant increase in peak expiratory flow rate (PEFR) after one session of smTAP which supports the feasibility and highlights the potential for further use in the future 10 . Furthermore, a recently published randomized controlled trial showed the superior efficacy of smTAP over EMST on improving reflex and voluntary cough 20 …”
Section: Introductionmentioning
confidence: 78%
“…The beneficial effects of EMST and smTAP on cough effectiveness has been shown in the literature. 8,10,20 These training modalities require repetitive and forceful exhaling (EMST) and coughing (smTAP) that increases the force applied to the vocal folds. The present study is the first to investigate the bulking and traumatic effects of these training modalities.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations